Innovate or domesticate. Projects between humans, animals, plants and machines - Jorge Camacho, Cristina (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
All animals from the areas affected by the tsunami disaster in Thailand in 2013 survived, except those that were domesticated. If we connect innovation with the term “de nuo” or “crecere”, as “novus” or “creare” for moving humanity forward, the link between wild animals and plants and environment will be a way of the survival of architectural world too. A technological advance toward the fluid origins of the living beings undoes shapes and affects building skin by a cohesive stability which responds to the energy used for manufacturing materials and taking advantage of atmospheric forces. Buildings respond to those forces simulating the behaviour of the environment by using software instead of doing it by instinct as wild animals. First at all, parametrics programming like Grasshopper allow for using complex geometrical and structural languages which are close to animal adaptations to dense flows; secondly, thermodinamics programming like Sinda/Fluint provide chemical process for manufacturinf new phase-change materials such as the mithological origins of acquatic plants; and, finally, network systems like Revit allowing full integration of structures, electrical installations and finishing such as the circulatory systems of the human body. To act like a fish is neccesary to apply the conditions of the environment for its own biological composition as the fish does, instead of having only its shape.
Keywords: Biomorphology; fluids; geometry; materials; building’s facilities